GROUP LEARNING STRATEGIES FOR ACADEMIC SUCCESS - Sabina Jumaboyeva Daler kizi; Ezoza Ismatovna Khazratkulova (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation:  The  topic  "Group  Learning  Strategies  for  Academic  Success" explores the importance and effectiveness of group learning in the educational process. Group  learning  allows  students  to  exchange  ideas,  develop  new  concepts,  and strengthen their knowledge. These strategies include various beneficial methods such as  discussion,  collaborative  problem-solving,  and  group  debates.  Such  learning processes ensure strong interpersonal connections and support among students, help develop  their  self-assessment  skills,  and  contribute  to  academic  success.  The effectiveness  of  group  learning  depends  on  collaboration  between  teachers  and students, and selecting the right methods is crucial for its successful implementation.